The Influence of Transformational Leadership Style and Work Motivation on Gen Z Worker Satisfaction in the Karawang Manufacturing Industry - Haifa Putri Utami; Linda Mora; Haryanti Mustika (CV. Era Digital Nusantara, 2026)
This study aims to determine the effect of transformational leadership style and work motivation on the satisfaction of Generation Z workers in the Karawang manufacturing industry. The problem raised is the level of job satisfaction that is influenced by leadership factors and worker work motivation. This study uses a quantitative approach with a causal associative method. The population in this study were Gen Z workers in a Karawang manufacturing company with 204 participants using a convenience sampling technique. Data collection was carried out using a Likert scale consisting of the Short Index Job Satisfaction (SIJS), Multifactor Leadership Questionnaire (MLQ), and The Motivation at Work Scale (MAWS). Data analysis was carried out using multiple linear regression with the help of SPSS. The results of the study indicate that transformational leadership style and work motivation have a significant effect on job satisfaction, both partially and simultaneously. This indicates that the better the implementation of the transformational leadership style and the higher the work motivation, the job satisfaction of Gen Z workers will increase.